(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the evolving role of mobile applications in modern English language learning by analysing three popular tools: ChatGPT, Word of the Day, and Learn English Grammar. Through an academic assessment of their pedagogical design, functionality, and limitations, the study proposes that these applications together form a complementary digital ecosystem that supports linguistic development. While ChatGPT offers interactive, personalised instruction, Word of the Day facilitates incremental vocabulary expansion, and Learn English Grammar provides structured grammatical practice. Despite inherent limitations, their combined use promotes autonomous learning and multimodal engagement, marking a significant progress in twenty-first-century language education.